Short-term effect of training and competition on muscle soreness and neuromuscular performance in elite rugby athletes - Tavares, F.; Healey, P.; Smith, T. B.; Driller, M. (Journal of Australian Strength and Conditioning, 2018)
Background: Muscle soreness is frequently utilized to monitor fatigue in athletes and is typically measured from a whole-body perspective, however, recent research recommends measuring muscle soreness across specific muscle sites. Therefore, the goal of the present study was to measure muscle soreness from different muscle sites within a group of elite Rugby union players. Methods: Nineteen elite Rugby players were monitored for muscle soreness obtained from 9 different muscle sites during a 9-day in-season period using a 5-likert scale likert scale (1- no soreness, 5 - maximal soreness). In addition, 13 of the 19 athletes performed countermovement jumps (CMJ) as a measure of neuromuscular performance to monitor fatigue. Results: No significant differences were observed for CMJ across days. A significant increase in muscle soreness from baseline was found for days 2, 3, 8 and 9 for all lower body muscles, while changes in upper body muscle soreness from baseline were only significant for days 8 and 9. When the average of the upper body (UB) and lower body muscle sites (LB) was calculated, it was found that UB soreness was significantly lower in comparison to both the LB soreness (days 2 and 3) and the average of whole body (WB) (days 5, 6 and 7). Conclusion: Lower body soreness of different muscle sites was more sensitive to training load in comparison to upper body. While one recovery day seemed to be adequate for UB to return to baseline, LB was still significantly elevated. Lower body and UB soreness scores remained significantly higher than baseline for at least two days following a match. Practical applications: Monitoring muscle soreness, in particular from the lower body, seems to provide important information for strength and conditioning coaches.